Distinct Cellular Mechanisms Underlie Smooth Muscle Turnover in Vascular Development and Repair. Issue 2 (19th January 2018) - Roostalu, Urmas; Aldeiri, Bashar; Albertini, Alessandra; Humphreys, Neil; Simonsen-Jackson, Maj; Wong, Jason K.F.; Cossu, Giulio
Abstract : Rationale: : Vascular smooth muscle turnover has important implications for blood vessel repair and for the development of cardiovascular diseases, yet lack of specific transgenic animal models has prevented it's in vivo analysis. Objective: : The objective of this study was to characterize the dynamics and mechanisms of vascular smooth muscle turnover from the earliest stages of embryonic development to arterial repair in the adult. Methods and Results: : We show that CD146 is transiently expressed in vascular smooth muscle development. By using CRISPR-Cas9 genome editing and in vitro smooth muscle differentiation assay, we demonstrate that CD146 regulates the balance between proliferation and differentiation. We developed a triple-transgenic mouse model to map the fate of NG2 + CD146 + immature smooth muscle cells. A series of pulse-chase experiments revealed that the origin of aortic vascular smooth muscle cells can be traced back to progenitor cells that reside in the wall of the dorsal aorta of the embryo at E10.5. A distinct population of CD146 + smooth muscle progenitor cells emerges during embryonic development and is maintained postnatally at arterial branch sites. To characterize the contribution of different cell types to arterial repair, we used 2 injury models. In limited wire-induced injury response, existing smooth muscle cells are the primary contributors to neointima formation. In contrast, microanastomosis leads to early smooth muscle death and subsequent colonization of the vascular wall by proliferative adventitial cells that contribute to the repair. Conclusions: : Extensive proliferation of immature smooth muscle cells in the primitive embryonic dorsal aorta establishes the long-lived lineages of smooth muscle cells that make up the wall of the adult aorta. A discrete population of smooth muscle cells forms in the embryo and is postnatally sustained at arterial branch sites. In response to arterial injuries, existing smooth muscle cells give rise to neointima, but on extensive damage, they are replaced by adventitial cells. Abstract : Supplemental Digital Content is available in the text.